Questioning the patient, questioning Hippocrates: Rufus of Ephesus and the limits of medical authority - Letts, M (2015)
Rufus of Ephesus's Quaestiones Medicinales is an under-studied work by one of the most respected doctors of Greco-Roman antiquity. This thesis presents a new translation – the first in English of the complete work – and a reassessment of the treatise. I propose that, far from being a simple handbook teaching doctors how to take a patient history, as has hitherto been assumed, QM is an ardent plea for doctors to recognise the limits of their own knowledge and the indispensability of questioning the patient. I argue that QM articulates the idea that the aim of medicine cannot be achieved through medical knowledge alone, and that, in constructing the patient as an essential partner in diagnosis and decisions about treatment, Rufus implies a sharing of authority between doctor and patient that is noticeably different from the emphasis that other authors, particularly the determinedly hierarchical Galen, place on securing patients’ obedience, a subject on which Rufus is noticeably silent. I argue that Rufus is unusual in the clarity and candour with which he perceives and acknowledges the limits of medical knowledge, in his conceptualisation of questioning as a discursive rather than a formulaic activity, in his explicit insistence that it must be addressed directly to the patient, in his psychological concept of habits, and in his recommendation of questioning as a strategy for resolving the tension between universal theory and individual experience. I look at modern cross-cultural research into the factors that drive patient compliance, and note that chief among them is patients feeling they are partners in the treatment process. This raises the question whether and to what extent the features that drive compliance are diachronically as well as cross-culturally consistent, and whether Rufus's shared authority model is more likely to have produced successful treatment outcomes than the autocratic paradigm promoted by Galen, and subsequently absorbed into Western medical tradition, that seems to have met with so much resistance.